ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN MODERN HIGHER EDUCATION SYSTEMS (International journal of artificial intelligence, 2026)
Artificial Intelligence technologies are becoming one of the leading factors transforming modern higher education systems worldwide. Universities increasingly integrate AI-based tools into teaching, learning management, scientific research, student assessment, and administrative processes. The application of machine learning algorithms, intelligent tutoring systems, natural language processing, predictive analytics, and adaptive learning platforms has significantly improved educational accessibility, personalization, and efficiency. This article analyzes the role of Artificial Intelligence technologies in higher education institutions, examines methodological approaches to AI implementation, evaluates the effectiveness of AI-supported educational models, and discusses challenges related to ethics, academic integrity, privacy, and digital inequality. The study is based on scientific literature, international reports, and empirical research findings from leading educational organizations and universities. The article demonstrates that AI technologies contribute to improving educational quality, increasing student engagement, optimizing administrative management, and enhancing data-driven decision-making in universities. At the same time, successful implementation requires strong digital infrastructure, teacher training, ethical regulations, and balanced human-AI collaboration.